KOMUNITAS KRISTEN DAN NABI ISA DALAM AL-QURAN - Greg. Soetomo (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
The Islamic response to Christianity (and Judaism) took place throughout the history and age of Islam itself. This is understandable because part of the definition of Islam is a response to both religions. There are several aspects of the life history of Prophet Muhammad and the context of the descent of revelation that requires explanation. Thus, there is a field of study of dialogue and diversity of faith that underscores discussion in the history of the revelation of the Qur'an. one question that will be answered in this paper is how the response of the Qur'an to the Christian community has a connection with formulating the identity of Prophet Isa? The question will be answered and approached by an explanation of four aspects: historical context, socio-political response, theological position, and Christian-Islamic relations.